1978
DOI: 10.1099/00207713-28-1-117
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas pseudoalcaligenes subsp. citrulli subsp. nov.

Abstract: Ten nonfluorescent Pseudomonas strains isolated from water-soaked lesions on cotyledons of plants of five Citrullus lanatus (watermelon) plant introductions were characterized and compared phenotypically with 22 other pseudomonads. The strains were distinguished phenotypically from other known plant pathogenic pseudomonads. The watermelon bacterium was aerobic. Cells were rod-shaped, gram negative, and motile by means of a single polar flagellum. They were nonfluorescent and grew at 41°C but not at 4°C. Oxidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
60
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 4 publications
6
60
0
Order By: Relevance
“…Schaad et al [41] described a non-fluorescent pseudomonad as the causal agent of a seedling blight of watermelon. The bacterium differed phenotypically from other known plant pathogenic pseudomonads and was classified as P. pseudoalcaligenes subsp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schaad et al [41] described a non-fluorescent pseudomonad as the causal agent of a seedling blight of watermelon. The bacterium differed phenotypically from other known plant pathogenic pseudomonads and was classified as P. pseudoalcaligenes subsp.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterium differed phenotypically from other known plant pathogenic pseudomonads and was classified as P. pseudoalcaligenes subsp. citrulli [41]. Later, Wall and Santos determined that the same organism caused a disease referred to as watermelon fruit blotch of mature watermelon fruit [42].…”
Section: Introductionmentioning
confidence: 99%
“…This compound can be considered a virulence factor because some strains are pathogenic but do not form cavities. Amylase, protease, pectinase and cellulase activities were mentioned as A. citrulli virulence factors (Schaad et al, 1978;Walcott et al, 2004;Burdman et al, 2005), but the role of such enzymes in A. citrulli virulence on fruit tissues remains to be determined (Burdman et al, 2005). In contrast, the production of amylolytic, proteolytic, pectolytic and cellulolytic enzymes was not detected in 41 A. citrulli strains, even if lipolytic activity was detected (Oliveira et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…At first, it was observed that the ATCC29625 type strain (obtained from watermelon) did not cause a hypersensitive response (HR) in tobacco and had little virulence on watermelon compared with other strains isolated from the same host (Schaad et al, 1978;Somodi et al, 1991). Furthermore, strains causing BFB epidemics in cantaloupe melon in Queensland, Australia were considerably more virulent on melon and less virulent on the invading plant Cucumis myriocarpus Naudin compared with strains obtained from watermelon in the same state (O´Brien and Martin, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The causal agent was reported as a serious seedborne pathogen of various plants such as rice (Shakya, 1987), watermelons, and cantaloupes (Schaad et al, 1978). It can be recovered from seeds using general agar medium (Song et al, 2000; but seedborne contamination of corn was not detected.…”
Section: Introductionmentioning
confidence: 99%